Transformasi Pelabelan Positif ke Pelabelan Negatif sebagai Ekspresi Kekerasan terhadap Guru dalam Karya Sastra Era Modern - Manurung, Rosida Tiurma (Zenit, 2013)
Nowadays, teachers are seen or regarded as figures who are underestimated, ridiculed, or even have no power. Transformation from positive to negative labeling is an expression of violence, in the sense that there is a phenomenon of negative image towards teachers as a result of improper behavior of students. School has become an arena where students express their attitude and behavior violently in order to marginalize teachers. In this research, teacher labeling from past literature is compared with the present one. The data are collected from 1960s to 2000s literature, whereas linguistic expressions  are  analyzed by means of Critical Discourse Analysis. The  research  method is descriptive and contrastive analysis, while the technique of data collection is library research and interview. It is hoped that through this research the labeling of teachers to be fading, robbed, deteriorating, and banished can be alleviated. As a result, teachers will regain their positive labeling. Teachers with positive image are absolutely necessary. Transformation of positive  labeling  will  result in a condusive, effective, interactive and optimal teaching-learning process. The transformation of positive labeling towards teachers has to be started soon. In fact, it is the task of writers and literary people to appreciate  teachers  and  respect their status.Keywords: transformasi pelabelan guru, ekspresi kekerasan, karya sastra era 1960-an, karya sastra era modern, analisis kontrastif, analisis wacana kritis